2015
DOI: 10.3399/bjgp15x686545
|View full text |Cite|
|
Sign up to set email alerts
|

Patient characteristics and frequency of bodily distress syndrome in primary care: a cross-sectional study

Abstract: BackgroundBodily distress syndrome (BDS) is a newly proposed diagnosis of medically unexplained symptoms, which is based on empirical research in primary care.AimTo estimate the frequency of BDS in primary care and describe the characteristics of patients with BDS.Design and settingA cross-sectional study of primary care patients in urban and rural areas of Central Denmark Region.MethodData were obtained from GP one-page registration forms, patient questionnaires (including a checklist for BDS), and national r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
4
29
1
3
Order By: Relevance
“…[26][27][28] Worse functional disability and poor physical health at baseline are reported to be associated with the persistence of UPS or high somatic symptom scores at 12-month followup. 11,12 Physical abuse in childhood was associated with an increase in somatic symptom severity at follow-up, suggesting that childhood physical abuse may have a long-term impact on physical health, similar to reports in other studies. [29][30][31][32] Implications for research and practice The current study suggests that for many patients in primary care with several bothersome UPS their symptoms may not be transient, and that around half will continue to be affected over time.…”
Section: Comparison With Existing Literaturesupporting
confidence: 83%
See 3 more Smart Citations
“…[26][27][28] Worse functional disability and poor physical health at baseline are reported to be associated with the persistence of UPS or high somatic symptom scores at 12-month followup. 11,12 Physical abuse in childhood was associated with an increase in somatic symptom severity at follow-up, suggesting that childhood physical abuse may have a long-term impact on physical health, similar to reports in other studies. [29][30][31][32] Implications for research and practice The current study suggests that for many patients in primary care with several bothersome UPS their symptoms may not be transient, and that around half will continue to be affected over time.…”
Section: Comparison With Existing Literaturesupporting
confidence: 83%
“…This is in line with comparatively more recent studies which have reported that around half continue to be burdened by their symptoms, albeit these studies include populations meeting the criteria for somatoform disorders 11 or bodily distress syndrome (BDS), which is a diagnosis of functional disorders rather than symptoms. 12 Only 11% in this present study reported their symptoms as resolved; this is also much lower than rates of resolution reported by Jackson and Passamonti in the US among consecutive primary care attenders at 3-month follow-up, although they did not distinguish between those with explained and unexplained symptoms. 9 Although at baseline one-third of the cohort in this study had clinically significant scores for depression and anxiety, neither depression nor anxiety independently predicted persistent somatic symptoms at follow-up.…”
Section: Comparison With Existing Literaturecontrasting
confidence: 82%
See 2 more Smart Citations
“…CBT is recommended in the Dutch multidisciplinary guideline for MUS and somatoform disorders and can be offered by the GP or in the specialized mental health care, if the GP considers the patient to be too complex or when the patient–doctor relationship is perturbed 40. In addition to the CBT for MUS and somatoform disorder, specialist psychiatric attention may be required for other mental health problems associated with physical symptoms (unexplained or explained) 2,42. Given that all people with physical symptoms (explained or unexplained) show more entry into primary care, but only people with MUS show more entry into specialized mental health care, MUS is apparently of higher influence than explained physical symptoms on the decision of the GP whether or not to refer to specialized mental health care.…”
Section: Discussionmentioning
confidence: 99%